Program renovasi dan pendampingan kelompok belajar untuk meningkatkan motivasi siswa pada masa pandemi covid-19 di Banjar Pacung Desa Sangeh Kecamatan Abiansemal, Kabupaten Badung Bali - Kariyana, I Made; Pratama, Octavianus Sumardana (Penamas: Journal of Community Service, 2022)
Study group assistance was carried out to increase students' motivation studying in Adya Kids study groups during the Covid-19 pandemic. The current condition of the study area cannot be called a proper place to study, so it is necessary to renovate the building and improve infrastructure so that students can learn comfortably and increase their motivation for learning enthusiasm. The current pandemic is not expected to be a barrier for students to reach their dreams in the future. Students are invited to remain enthusiastic in understanding the material given at school. During pandemic the Covid-19, students can understand and apply the correct health protocols in carrying out learning activities. In addition, the existing old buildings need to be renovated and built-in conditions suitable for study. The results obtained in the mentoring of students' understanding of health protocols and increased interest in learning are indicated by good end-of-semester grades. In addition, the renovated building in the Adya Kids study group is also suitable and comfortable for students to study.